In Vitro Antioxidant and Insulin Mimetic Activities of Heteroleptic Oxovanadium(IV) Complexes with Thiosemicarbazones and Naproxen. Issue 21 (2nd June 2020) - Bharathi, Sundaram; Mahendiran, Dharmasivam; Senthil Kumar, Raju; Kalilur Rahiman, Aziz
Abstract: Six heteroleptic oxovanadium(IV) complexes with general formula [VOL 1–6 (nap)], where, L 1–3 =2‐(1‐(4‐substitutedphenyl)ethylidene)hydrazinecarbothioamide, L 4–6 =2‐(1‐(4‐substitutedphenyl)ethylidene)‐ N ‐methylhydrazinecarbothioamide and nap=naproxen, have been synthesized and characterized. FTIR spectra exhibit a strong band between 965 and 991 cm −1, characteristic of υ(V=O) stretching vibration. UV‐Vis and theoretical studies suggested distorted square‐pyramidal geometry and oxidation state of vanadium(IV) with d 1 configuration was confirmed by EPR spectra. Cyclic voltammograms exhibit metal based irreversible redox peaks corresponding to one electron oxidation (+0.83 to +0.70 V) and reduction (−0.69 to −0.53 V) processes. In vitro antioxidant studies revealed that complexes containing electron donating substituent (−CH3 ) showed higher activity. In vitro antidiabetic activity of complexes with enzymes like α‐amylase, α‐glucosidase and glucose‐6‐phosphatase made them better inhibitors of insulin, which is further supported by in silico studies, and complex 6 shows better in vitro insulin mimic activity against insulin responsive 3T3‐L1 adipocyte cells compared to insulin and metformin. Abstract : A series of heteroleptic oxovanadium(IV) complexes containing thiosemicarbazones as the main ligand and naproxen as auxiliary ligand with general formula [VOL 1–6 (nap)] (1 –6 ), where L 1–3 =2‐(1‐(4‐substitutedphenyl)ethylidene)hydrazinecarbothio‐amide, L 4–6 =2‐(1‐(4‐substitutedphenyl)ethylidene)‐ N ‐methylhydrazinecarbothioamide and nap=naproxen were synthesized, which showed non‐cytotoxic nature towards 3T3‐L1 adipocyte cells and higher glucose uptake ability. In vitro inhibition against glucose‐6‐phosphatase, α‐amylase and α‐glucosidase enzymes showed better activity compared to the standard drugs, acarbose and metformin.